Large conductance voltage-and calcium-activated K+ (BK) channel in health and disease - Echeverría, Felipe; Gonzalez-Sanabria, Naileth; Alvarado-Sanchez, Rosangelina; Fernández, Miguel; Castillo, Karen; Latorre, Ramon (Frontiers in Pharmacology, 2024)
Large Conductance Voltage- and Calcium-activated K+ (BK) channels are transmembrane pore-forming proteins that regulate cell excitability and are also expressed in non-excitable cells. They play a role in regulating vascular tone, neuronal excitability, neurotransmitter release, and muscle contraction. Dysfunction of the BK channel can lead to arterial hypertension, hearing disorders, epilepsy, and ataxia. Here, we provide an overview of BK channel functioning and the implications of its abnormal functioning in various diseases. Understanding the function of BK channels is crucial for comprehending the mechanisms involved in regulating vital physiological processes, both in normal and pathological conditions, controlled by BK. This understanding may lead to the development of therapeutic interventions to address BK channelopathies.